Genetic parameter estimates for prenatal and postnatal mortality in Nellore cattle - Magalhães Silva, L. C. [UNESP]; Baldi, F. [UNESP]; Aboujaoude, C. [UNESP]; Venturini, G. C. [UNESP]; Albuquerque, L. G. [UNESP]; Paranhos da Costa, M. J.R. [UNESP] (Wiley, 2017)
The aim of this study was to estimate genetic parameters for prenatal (PRE) and postnatal (POS) mortality in Nellore cattle. A total of 13 141 (PRE) and 17 818 (POS) records from Nellore females were used. PRE and POS were recorded using binary scale scores: a score of ‘1’ was given to calves that were born alive (PRE) and those that were alive at weaning (POS), and a score of ‘0’ was given to calves that were not alive at or around birth (PRE), as well as to those weighed at birth but not at weaning (POS). The relationship matrix included 698 sires, 107 paternal grandsires and 69 maternal grandsires. Data were analysed using Bayesian inference and a sire–maternal grandsire threshold model, including contemporary groups as random effects, and the classes of dam age at the beginning of mating season (for PRE), and dam age at calving and birthweight (linear covariable) (for POS), as fixed effects. For both traits, the covariance between direct and maternal effects (rD ,M) was estimated (rD ,M≠ 0) or fixed at zero (rD ,M = 0). PRE and POS rates were 3.00 and 4.04%, respectively. Estimates of direct and maternal heritability were 0.07 and 0.17, respectively, for PRE, and 0.02 and 0.07, respectively, for POS, assuming rD ,M = 0. For rD ,M ≠ 0, these estimates were 0.07 and 0.12, respectively, for PRE, and 0.03 and 0.07, respectively, for POS. The correlation estimates between direct and maternal effects were −0.71 (PRE) and −0.33 (POS). PRE and POS show low genetic variability, indicating that these traits probably suffer major environmental influences. Additionally, our study shows that the maternal genetic component affects preweaning calf mortality twice as much (or more) as the direct genetic component. A large number of offspring per sire is necessary in progeny tests to genetically decrease calf mortality.
Keywords: Beef cattle; calf survival; correlations; heritability; threshold model